Information Technology and Repositioning of Human Resource Management Functions - Misbachul Munir; Mohammad Djaelani (metromedia.education, 2022)
Technological developments have an impact on business development. Almost all business functions must make changes to anticipate them. This fact becomes a challenge for business practitioners and academics who study management science. A concrete example that shows the impact of technological advances on the business world is the development of VoIP (Voice Over Internet Protocol). In response to this, business transformation is an urgent thing to do. Advances in information technology have an impact on changing business organizations from a hierarchical business organization to a leaner business organization. The transformation of the HRM role has led to several new concepts in contemporary HRM practice. The repositioning of the HRM function is also an anticipation of changes in the global business environment. The repositioning of the HRM function from an academic point of view should trigger more comprehensive research in analyzing this process.